Red Hat OpenShift fundamentals : LiveLessons (LiveLessons (Indianapolis, Ind.), 2019)
"Red Hat OpenShift Fundamentals LiveLessons provides an introduction to working with containers in an OpenShift environment, and covers all core aspects of working with containers in OpenShift. OpenShift is an increasingly popular platform that helps you more easily deploy applications in an enterprise environment. The platform helps developers to seamlessly roll out an application in the form of a completely operational container. At the same time, it allows administrators to manage the application life cycle in a flexible way, where applications can be monitored for availability, and easily scaled up and down if the workload requires it. Learn how to get started with OpenShift in six lessons. In the first lesson, you'll learn how OpenShift can help you. An explanation of what OpenShift is, and how it relates to the Kubernetes platform is provided. The second lesson discusses how to get started with OpenShift, and different installation scenarios are demonstrated. Lesson 3 shows how to deploy applications in OpenShift, and Lesson 4 will explain software-defined networking, as implemented in OpenShift. Lesson 5 discusses more advanced features, such as pod scaling and node placement; and Lesson 6 shows how to connect containers in OpenShift to storage. With a combination of white-board instruction, demonstrations, and CLI learning, Sander van Vugt demystifies OpenShift."--Resource description page